1984
DOI: 10.1002/1097-0142(19841201)54:11<2363::aid-cncr2820541110>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Complications following postoperative combined radiation and chemotherapy in adenocarcinoma of the rectum and rectosigmoid: A randomized trial that failed

Abstract: A randomized multicenter trial was started to evaluate the effect of irradiation combined with 5‐fluorouracil and methotrexate on survival after surgery for rectal and rectosigmoidal carcinoma, Dukes' stages B and C. The trial was terminated prematurely after entrance of 34 patients due to frequent and serious complications. Three patients died as a direct consequence of the adjuvant treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1986
1986
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…It is well known that RT may be a cause of intra‐abdominal adhesion formation [25]. Many reports regarding irradiation complications including bowel obstruction have been published [11–15,25–28]. According to these studies, the rate of bowel obstruction due to intra‐abdominal adhesions ranges from 4.9% to 38.5%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that RT may be a cause of intra‐abdominal adhesion formation [25]. Many reports regarding irradiation complications including bowel obstruction have been published [11–15,25–28]. According to these studies, the rate of bowel obstruction due to intra‐abdominal adhesions ranges from 4.9% to 38.5%.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the colorectal procedure is a major cause of adhesive intestinal obstruction. Moreover, it has been reported that the risk of bowel obstruction is higher in patients receiving adjuvant RT than in those undergoing only surgical resection [11–14]. Montz et al .…”
Section: Introductionmentioning
confidence: 99%
“…Dve velike studije, jedna u Danskoj i druga u Holandiji u kojima je primenjen protrahovani režim preoperativne standradno frakcio-nisane terapije zračenjem pokazale su značajno smanjenje lokalnog recidiva u odnosu na kontrolnu grupu bolesnika kod kojih je lečenje bilo isključivo hirurško, uz značajno produženje DFI intervala i s neznatno manjim procentom perioperativnog mortaliteta i morbiditeta, u odnosu na prethodno prijavljene [18,19].…”
Section: Preporuke Za Selekciju Bolesnika Za Primenu Neoadjuvantne Teunclassified